Cardiovascular Disease and Mortality in Adults Aged ≥60 Years According to Recommendations by the American College of Cardiology/American Heart Association and American College of Physicians/American Academy of Family Physicians. Issue 2 (February 2019) - Jaeger, Byron C.; Anstey, D. Edmund; Bress, Adam P.; Booth, John N.; Butler, Mark; Clark, Donald; Howard, George; Kalinowski, Jolaade; Long, D. Leann; Ogedegbe, Gbenga; Plante, Timothy B.; Shimbo, Daichi; et al.
Abstract : In 2017, the American College of Cardiology/American Heart Association (ACC/AHA) and the American College of Physicians/American Academy of Family Physicians (ACP/AAFP) published blood pressure guidelines. Adults recommended antihypertensive medication initiation or intensification by the ACP/AAFP guideline receive the same recommendation from the ACC/AHA guideline. However, many adults ≥60 years old are recommended to initiate or intensify antihypertensive medication by the ACC/AHA but not the ACP/AAFP guideline. We compared atherosclerotic cardiovascular disease event rates according to antihypertensive treatment recommendations in the ACC/AHA and ACP/AAFP guidelines among adults ≥60 years old with systolic blood pressure ≥130 mm Hg or diastolic blood pressure ≥80 mm Hg in the REGARDS study (Reasons for Geographic and Racial Differences in Stroke) and the JHS (Jackson Heart Study). Among 4311 participants not taking antihypertensive medication at baseline, 11.4%, 61.2%, and 27.4% were recommended antihypertensive medication initiation by neither guideline, the ACC/AHA but not the ACP/AAFP guideline, and both guidelines, respectively. Atherosclerotic cardiovascular disease event rates (95% CI) for these groups were 3.4 (1.6–5.2), 18.0 (16.1–19.8), and 25.3 (21.9–28.6) per 1000 person-years, respectively. Among 7281 participants taking antihypertensive medication at baseline, 57.9% and 42.1% were recommended antihypertensive medication intensification by the ACC/AHA but not the ACP/AAFP guideline and both guidelines, respectively. Atherosclerotic cardiovascular disease event rates (95% CI) for these groups were 18.2 (16.7–19.7) and 33.0 (30.5–35.4) per 1000 person-years, respectively. In conclusion, adults recommended initiation or intensification of antihypertensive medication by the ACC/AHA but not the ACP/AAFP guideline have high atherosclerotic cardiovascular disease risk that may be reduced through treatment initiation or intensification. Abstract : Supplemental Digital Content is available in the text.